Checklist of the families Opetiidae and Platypezidae (Diptera) of Finland - Ståhls, Gunilla (ZooKeys, 2014)
A checklist of the Opetiidae and Platypezidae (Diptera) recorded from Finland.
Keywords: checklist; diptera; Finland; opetiidae; Platypezidae

New data on Platypezidae and Opetiidae (Diptera) of Finland - Ståhls, Gunilla; Kahanpää, Jere (Sahlbergia, 2006)
Six species of flatfooted flies, Platypezidae, are reported as new to Finland based on authors investigations during years 2003-2005. Detailed information of Finnish records as well as data on host fungus association and habitat of adults are given. This study reports the first confirmed breeding record for Agathomyia lundbecki from Inonotus radiatus, and recorded Platypezina connexa repeatedly as bred from strongly decayed and softened trunk of spruce.
Keywords: Agathomyia; diptera; Finland; Platypezidae; Platypezina